Hubungan Pengetahuan dan Konsumsi Makanan Cepat Saji dengan Status Obesitas Remaja di SMP Negeri 2 Abiansemal - Anggara, I Made Yoga Ary; Sukraniti, Desak Putu; Suarjana, I Made (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2025)
Obesity is a pathological condition where excess fat accumulates in the body which is influenced by several factors, one of which is consumption and knowledge. The aim of this research is to determine the relationship between knowledge and consumption of fast food and the obesity status of adolescents at SMP Negeri 2 Abiansemal. This type of observational research was carried out in February 2023 at SMP Negeri 2 Abiansemal, with 76 samples. The sample collection technique uses the Multistage Random Sampling method. Consumption data uses 1x24 hour recall collected over 2 days. Knowledge data was collected using a knowledge form through interviews. The data are presented in frequency tables and cross tables between knowledge and consumption of fast food macronutrients and between consumption of fast food macronutrients and obesity status. The results of the Spearman rank analysis test show that there is a relationship between knowledge and fast food protein consumption (p = 0.000, r = -0.718). There is a relationship between knowledge and consumption of fast food fats (p = 0.000, r = 0.438). There is a relationship between protein consumption and obesity status (p = 0.000, r = 0.826). There is a relationship between fat consumption and nutritional status (p = 0.000, r = -0.507). It is hoped that schools can provide education to students, canteens and shops about nutritionally balanced food and it is hoped that future researchers can explore other factors that cause obesity by using more appropriate methods such as SQ-FFQ.